Budaya Bendawi Pra Islam di Keraton Cirebon Indonesia - Wahyu Iryana; Muhamad Bisri Mustofa; Muhammad Saidun Anwar (Bulletin of Indonesian Islamic Studies, 2023)
Legacy of Sunan Gunung Djati Existing in Cirebon are mosques and palaces which are full of pre-Islamic material elements, both architecturally and objects from the past. This paper aims to explore pre-Islamic material elements in the Cirebon palace and analyze their meaning. The method used in this research is explorative-descriptive, namely one of archaeological research, research by exploring the place under study to look for the desired problem and try to describe it. Based on research, it can be concluded that: first, there are many pre-Islamic elements including, the Barong Lion Train (a train used for the purposes of the sultans), Kamasutera Carvings (reliefs depicting sexual activities), Nandi Statues (vehicles of Lord Shiva and Goddess Parwati), Lingga Yoni (Phallus symbolizing the male genitalia; Yoni symbolizes female genitalia), Bentar Temple (the entrance building of a temple-shaped temple that is split in half), the Derum Elephant Statue on the water (Gajah Derum Tirta Linuih; shows 1458 Saka), the Garuda Statue wrapped around a Snake (Bujnagga Ratu Obahing Bumi; shows 1618 Saka), The Firearms relief Monument (Braja Asta Rasaning Bumi: 1625 Saka), Lotus or Lotus (spiritual symbol symbolizing purity), The Garuda Mina stretcher (a vehicle for the sultans' children to be circumcised), Surya Majapahit (found on the mihrab of the Great Mosque of Cirebon; is the symbol of the Majapahit Kingdom), Ganesaha Carvings (scientific symbols in Hindu mythology), and Jaladwara (a hole to release water in a temple). Secondly, the existence has the meaning of friendship with other countries at that time such as China, India, and Arabia, it was found on the Barong Lion Train. In addition to this, the existence of pre-Islamic elements is a process of acculturation carried out by Sunan Gunung Djati to captivate the hearts of the people of Cirebon to know and embrace Islam.